Implementation of Agile Method in Village Web Development (Case Study: Tapus Village) - Rahma Pita Kurnia; Fajriyah; Jepri Yandi (Yayasan Kita Menulis, 2026)
The advancement of information technology has had a significant impact on various aspects of life, including governance at the village level. However, Tapus Village still relies on traditional methods such as bulletin boards, community meetings, and WhatsApp groups to disseminate information to its residents. These methods have limitations in terms of reach, effectiveness, and information archiving. To address these issues, this study aims to develop a village website for Tapus Village using the Agile Software Development methodology. Agile was chosen due to its flexible and adaptive approach, allowing the system to evolve in response to users’ changing needs. The outcome of this research is a village website capable of presenting activity updates and important announcements in a structured and easily accessible format. With the implementation of this website, Tapus Village is expected to enhance transparency, improve service efficiency, and increase community engagement in village development. Moreover, this study demonstrates that the Agile method is effective for developing web-based information systems in village government environments with limited resources.